(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Overactive bladder is a common syndrome, causing a significant burden regarding both health and cost for patients. Mirabegron is a new drug with many clinical and economic advantages compared to the previous antimuscarinic group - represented by Solifenacin, the only drug that is co-paid by Vietnam Health Insurance. This systematic review was performed with the aim of systematically reviewing efficacy, safety, and cost-effectiveness evidences of Mirabegron versus Solifenacin for the treatment of overactive bladder. Research methods: The literature was comprehensively searched across the databases PubMed and Web of Science up to October 2022. Studies were included if they reported the efficacy, safety, and cost-effectiveness of Mirabegron compared with Solifenacin cleared the inclusion and exclusion criteria. The CONSORT, STROBE and CHEERS checklists were used to assess study quality. Research results: After two rounds of title/abstract and full text filtering, 16 studies were selected for the systematic review on efficacy and safety and 4 studies were selected for the systematic review on cost-effectiveness. Efficacy and safety studies, including clinical trials and observational studies, were conducted in many countries around the world in many different geographical areas. Studies show that Mirabegron is equally effective compared to Solifenacin, but Mirabegron’s tolerability is better. Cost-effectiveness studies show that Mirabegron is cost-effective compared to Solifenacin in the treatment of overactive bladder. Conclusion: Studies worldwide show that Mirabegron is equally effective but has better tolerability and is cost-effective when compared to Solifenacin in the treatment of overactive bladder.